Importance of understanding Vata Dosha and Trayopastambha in the management of diseases - Mishra, Ayushi; Singh, Pratibha; Agrawal, Monika; Kumari, Meena; Tiwari, Ramanand; Kumar Mandal, Sisir; Upadhyay, Garima; S Byadgi, Parameswarappa (International Journal of Psychosocial Rehabilitation, 2024)
The human body has a unique mixture of three doshas (vata, pitta, kapha), which trigger life.These three doshas perform different functions in the body. When these defects areimbalanced, various types of physical and mental diseases are generated. Treatment ofdiseases is also possible on the basis of the panch mahabhoot that make up the body.According to the three stages of dosha (Sanchaya, prakop, prasar), symptoms of diseasesarise. Acharya Charaka has given the following reasons for various Nanatmaja disorders -  Nature, Adhyanthana, Gender, Volume, Ruja, Varna, Naam.Dosa outbreaks play animportant role as they are responsible for the occurrence of diseases when consumed in largeamounts.Therefore, this article describes the vata prakop nidana to overcome vatajnanatmaja disorder